Analisis Aktivasi Neutron (AAN) Logam Magnesium dan Mangan dalam Air PDAM setelah Prekonsentrasi Menggunakan Dietilditiokarbamat - Eva S. Simaremare; Yati B. Yuliati; Dadang Supriyatna (Jurusan Biologi FMIPA Universitas Cenderawasih, 2013)
Tracer metal (ng/g) elements in water can be determined solely by a qualitative or quantitative analysis using preconcentration method. This method improves the sensitivity of Neutron Activation Analysis (NAA) into part per billion (ppb) levels, therefore the type and quantity of metal in the water of PDAM can be determined. Preconcentration method was performed by adding diethyldithiocarbamate (DDC) into water sample to produce complex metal sediment. The sediment was irradiated inside TRIGA 2000 reactor in P3TkN for 3 minutes with the pneumatic tube facilities and readusing γ-ray spectrometer. The result ensures diethyldithiocarbamate is possible to apply in preconcentrated method for NAA, the alkali and halogen disturbance ions could also be reduced. Quantitatively, elements in PDAM water are natrium, aluminium, clorine, zirconium, iodine, calcium, manganese, and magnesium. The magnesium and manganese concentration was 0.1 and 0.06 ng/mL.Key words: Neutron Activation Analysis, preconsentration, dietilditiokarbamat, magnesium, manganese.